2018
DOI: 10.1093/mnras/sty1026
|View full text |Cite
|
Sign up to set email alerts
|

OJ287: Deciphering the “Rosetta stone of blazars★”

Abstract: OJ287 is the best candidate active galactic nucleus (AGN) for hosting a supermassive binary black hole (SMBBH) at very close separation. We present 120 Very Long Baseline Array (VLBA) observations (at 15 GHz) covering the time between April 1995 and April 2017. We find that the OJ287 radio jet is precessing on a time-scale of ∼22 yr. In addition, our data are consistent with a jet-axis rotation on a yearly time-scale. We model the precession (24 ± 2 yr) and combined motion of jet precession and jet-axis rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
210
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(223 citation statements)
references
References 90 publications
13
210
0
Order By: Relevance
“…From the analysis of the ridgeline of contours, the former has argued the jet to be a rotating helix. In contrast, a reanalysis of the same by data Britzen et al [47] in combination with other observations have reported additional yearly variations under the assumption that observed changes are smooth. Based on these morphological changes, Britzen et al [47] have favored a precessing jet for the cause and claims that this can explain both radio and optical variations within this framework.…”
Section: Imagingmentioning
confidence: 83%
See 3 more Smart Citations
“…From the analysis of the ridgeline of contours, the former has argued the jet to be a rotating helix. In contrast, a reanalysis of the same by data Britzen et al [47] in combination with other observations have reported additional yearly variations under the assumption that observed changes are smooth. Based on these morphological changes, Britzen et al [47] have favored a precessing jet for the cause and claims that this can explain both radio and optical variations within this framework.…”
Section: Imagingmentioning
confidence: 83%
“…In contrast, a reanalysis of the same by data Britzen et al [47] in combination with other observations have reported additional yearly variations under the assumption that observed changes are smooth. Based on these morphological changes, Britzen et al [47] have favored a precessing jet for the cause and claims that this can explain both radio and optical variations within this framework. Correlation studies between mm radio time series with other bands (optical to γ-rays) have found a strong connection between these during the high activity periods with the increased activity associated with radio-flaring in quasi-stationary features and ejection of superluminal features [86,87].…”
Section: Imagingmentioning
confidence: 83%
See 2 more Smart Citations
“…The well-studied AGN OJ 287 putatively hosts a SMBHB, inferred through a pair of periodic optical outbursts every ∼12 years (e.g., Sillanpaa et al, 1988;Valtonen et al, 2011) resulting from the impinging of the accretion disk of the primary by the secondary SMBH at these intervals during its orbital motion (e.g., Lehto & Valtonen, 1996). However, the recent study of Britzen et al (2018) notes that jet precession can explain the periodic variability though the driver of precession may still be a SMBBH.…”
Section: Introduction and Motivationsmentioning
confidence: 99%